La erupción del volcán Irazú 1917-1921 (Costa Rica): dinámica y entorno social - Mora Fernández, Mauricio (2024)
This study reconstructs and analyzes, from a volcanological and historical approach, the 1917-1921 eruptive phase of the Irazú volcano based on newspaper, documental, technical-scientific and historical sources. The results are consistent with the known tephrostratigraphy and new aspects of the eruption are given, such as: the description of strombolian eruptions, tephra fall reconstructions for relevant eruptions and the detail analysis of the November 30, 1918 (VEI~3) vulcanian eruption. The convergence of this natural event with the dictatorship of "the Tinoco" between 1917 and 1919 is analyzed as well as how both events abruptly burst into the life of Costa Rican society, especially in San José, the capital of Costa Rica. The impact of the eruptive phase 1917-1921 was minor compared to that of 1963-65, but not negligible, and the adverse political climate of the time contributed to overshadow it. All this made a deeper analysis and quantification of its impact difficult. The study of the eruptive phase of 1917-1921 is fundamental to evaluate risk scenarios based on the characteristics of Costa Rica in the 21st century and thus contribute to an adequate risk management.